2014
DOI: 10.1186/1471-2229-14-80
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between starch synthase I and branching enzyme isozymes determined using double mutant rice lines

Abstract: BackgroundStarch is the most important carbohydrate in plant storage tissues. Multiple isozymes in at least four enzyme classes are involved in starch biosynthesis. Some of these isozymes are thought to interact and form complexes for efficient starch biosynthesis. Of these enzyme classes, starch synthases (SSs) and branching enzymes (BEs) play particularly central roles.ResultsWe generated double mutant lines (ss1/be1 and ss1 L /be2b) between SSI (the largest component of total soluble SS activity) and BEI or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 33 publications
9
64
0
Order By: Relevance
“…This adds considerable weight to the argument that it is the heteromeric complexes which are the functionally active components during amylopectin biosynthesis. Similar changes in the starch granule proteome have been observed in rice mutants (Abe et al 2014) where mutation in SBEIIb led to the appearance of SBEI in granules. In wheat, barley and rice mutants which lack a functional SSIIa (Yamamori et al 2000;Morell et al 2003;Umemoto and Aoki 2005), the granules also become devoid of SSI and SBEII class proteins.…”
Section: Genetic Evidencesupporting
confidence: 63%
“…This adds considerable weight to the argument that it is the heteromeric complexes which are the functionally active components during amylopectin biosynthesis. Similar changes in the starch granule proteome have been observed in rice mutants (Abe et al 2014) where mutation in SBEIIb led to the appearance of SBEI in granules. In wheat, barley and rice mutants which lack a functional SSIIa (Yamamori et al 2000;Morell et al 2003;Umemoto and Aoki 2005), the granules also become devoid of SSI and SBEII class proteins.…”
Section: Genetic Evidencesupporting
confidence: 63%
“…These include reactivity toward various glucans including branched glucans (amylopectin and glycogen), amylose, and malto-oligosaccharides (MOS) (Tetlow 2012); chemicals such as cyclodextrins (Vikso-Nielsen and Blennow 1998), phosphorylated metabolites (Morell et al 1997), and citrate (Hamada et al , 2002; temperature dependence of activities Hamada et al 2002;Ohdan et al 2011;Sawada et al 2013); and association with starch granules (Rahman et al 1995;Mu-Forster et al 1996;Hamada et al 2001Hamada et al , 2002Grimaud et al 2008;Liu et al 2012b;Abe et al 2014). For other properties of BE, see review by Tetlow (2012).…”
Section: Structures and Basic Enzymatic Propertiesmentioning
confidence: 96%
“…In rice endosperm, protein-protein interactions occur between or among starch synthases (SSs), branching enzymes (BEs), pullulanase, and OsPho1 (21). In wheat, it has been reported that Pho1 interacts with BEI and BEIIb in an ATP-dependent manner in soluble extracts of developing endosperms harvested at mid-to-late developmental stage (14).…”
mentioning
confidence: 99%